Commentary on Future of Health Behavior Research: Aging Perspectives - Marcia G. Ory (New Prairie Press, 2017)
This Commentary provides personal reflections on the future of health behavior research and the role of AAHB in the preparation of the next generation of researchers and educators for high quality relevant research and practice. Comments center around the four questions presented to Research Laureates at the 2017 AAHB Annual Meeting. Themes include: 1) a life-course perspective as a priority game changer in furthering health behavior research; 2) multiple disciplines to advance health behavior research; 3) pathways to a successful doctoral program; and 4) forward thinking for identifying risk factors for public health problems and contextually-based health behavior solutions.